19th April International Academic Conference on Economic and Social Development, 10–13 April 2018, Moscow, Higher School of Economics - .. . (Экономическая социология, 2017)
19th April International Academic Conference on Economic and Social Development, 10–13 April 2018, Moscow, Higher School of Economics